Courier Assistant Service Practices at Shopee Express Courier Partners from a Contract Law Perspective - Wulandari, Sekar Ajeng; Fuqoha (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study analyzes the practice of assistant couriers employed by Shopee Express partner couriers from a contract law perspective. The relationship between Shopee Express and partner couriers is governed by a legally binding partnership agreement. However, the existence of assistant couriers hired by partner couriers lacks a clear legal basis within the agreement. This phenomenon raises potential legal issues, particularly concerning liability for lost or damaged goods during delivery. Based on the principle of freedom of contract in Article 1338 of the Indonesian Civil Code, partner couriers and Shopee Express have the right to agree on the terms of their employment contract. However, the use of assistant couriers without Shopee Express’s approval may violate the validity conditions of contracts under Article 1320 of the Indonesian Civil Code. This study recommends that Shopee Express establish clearer regulations regarding the involvement of assistant couriers to ensure legal certainty and protection for all parties involved.